EFFECT OF JOB STRESS ON ACADEMIC PERFORMANCE AMONG UNDERGRADUATE STUDENTS OF THE OPEN UNIVERSITY OF SRI LANKA (Proceedings of the International Conference on Social Sciences, 2024)
Job stress is the harmful physical and emotional responses that occur when the requirements of the job do not match the capabilities, resources, or needs of the worker. Compared to other universities, the Open University has most students who are engaged in various professional careers. In the context of Open and Distant Learning (ODL), Open university students has become a problem to manage their work stress balance while studying. The purpose of this research is to sociologically study the effect of job stress on the academic performance of the university among undergraduate students at the Open University of Sri Lanka. This study further aims to present the causes of job stress as well as the measures to be taken to control and prevent it. This study is quantitative research and used a questionnaire to collect data. In identifying the sample selected for the research on the effect of job stress on the academic performance of the university among undergraduate students of the Open University of Sri Lanka, the Department of Social Studies was selected for the sample among the departments of the Open University of Sri Lanka. This study was conducted through a non-random sample as a judgmental sample of 40 employed students from the B.A. in Social Sciences degree program’s student population. Using employed students for this study, Participants who reported experiencing higher levels of job stress had lower grades and academic achievement compared to those who reported lower levels of job stress. Most of the participants reported experiencing moderate to high levels of job stress, which was found to be negatively impacted by factors such as workload, job demands, and work-life balance. Here, some suggestions for the control and prevention of job stress were presented through this study. In conclusion, this study emphasizes the negative impact of job stress on academic performance.
Keywords: job stress; academic performance; undergraduates; judgmental sample; Open and Distance Learning (ODL)